Familial factors predicting recovery and maintenance of physical activity in people with low back pain: Insights from a population‐based twin study. (21st September 2018) - Zadro, Joshua Robert; Shirley, Debra; Duncan, Glen E.; Ferreira, Paulo H.
Abstract: Background: It is unknown how familial factors influence the recovery from low back pain (LBP) and the maintenance activity behaviours. We aimed to investigate whether individual and within‐family physical activity (PA) and sedentary behaviour influenced recovery from LBP, and maintenance of PA and sedentary behaviour in people with and without LBP. Methods: Longitudinal logistic regression analyses were performed on adult twins from the Washington State Twin Registry. First, individual and within‐family (based on co‐twin data) sufficient PA (at least 75 min of vigorous‐intensity PA, or 150 min of moderate‐intensity PA per week) and high leisure sitting time (≥3 hr/day) were our exposure variables (baseline). LBP within the past 3 months at follow‐up defined non‐recovery (outcome). Second, within‐family sufficient PA and high leisure sitting time were our exposure variables(baseline) and our outcomes were individual PA and sitting time at follow‐up. All analyses were adjusted for follow‐up length (range: 1–7 years) and confounding variables. Results: Individual and within‐family PA and sitting time were not associated with recovery. Within‐family PA and sitting time predicted individual maintenance of PA (OR = 1.47, 95% CI: 1.17–1.84, n  =   1, 388 twins) and sitting time (OR = 1.41, 95% CI: 1.10–1.82, n  =   1, 534). Within‐family PA and sitting time had the strongest effects on those without (OR = 1.79, 95% CI: 1.33–2.41, n  =   788) and with LBP (OR = 1.90, 95% CI: 1.32–2.76, n  =   698), respectively. Conclusion: Having active family members increased the likelihood of continuing to be active (particularly for those without LBP), while having sedentary family members increased the likelihood of maintaining sedentary behaviours (particularly for those with LBP). Significance: This study was the first to investigate how familial activity behaviours influence recovery from LBP and ongoing activity behaviours. People with LBP living within a sedentary family likely require specific interventions to reduce their sedentary behaviours.